Factors Predicting Acute Kidney Injury Among Critically lll Older Patients After Non-Cardiac Surgery - Pipattanawarrakhun, Narin; Chayaput, Prangtip; Wirojratana, Virapun; Chanruangvanich, Wallada (Journal of Thailand Nursing and Midwifery Council, 2021)
Objective: To examine the predictive power of preoperative hemoglobin, the revised cardiac risk index, peri-operative erythrocyte transfusion, and time of operation toward acute kidney injury among critically ill older patients after non-cardiac surgery. Design: Retrospective predictive correlational design with cross-sectional study Methodology: The researcher recruited a total sample of 278 older patients who met the criteria, aged 60 years and over, received any major surgeries except cardiac surgery and were admitted to Intensive Care Unit after surgery. Data were analyzed using descriptive statistics and binary logistic regression. Roy adaptation model was employed as a conceptual framework for explaining physiologic adaptation. Results: Most of samples were females with an average age of 74.77 years (SD=8.35).An occurrence of post-operative acute kidney injury was 50%. The predictive power analysis results illustrated that pre-operative hemoglobin, revised cardiac risk indexes, received peri-operative erythrocyte transfusion and time of operation could jointly predict acute kidney injury with explained variance of 52.4% (Nagelkerke R2=.524). The findings also revealed that pre-operative hemoglobin indicating anemia, revised cardiac risk indexes at high risk, peri-operative erythrocyte transfusion more than 500 ml., less than or equals to 500 ml., and time of operation equal or more than 120 minutes could put the critically ill older patients after non-cardiac surgery at risk of acute kidney injury for 3.779, 8.819, 7.154, 2.141 and 3.560 times, respectively. Recommendation: The study findings could be utilized as a clinical information for planning nursing care of critically ill older patients undergoing non-cardiac surgeries at ICU admission describing physiologic adaptation by Roy adaptation model. In addition, nurses should closely monitor acute kidney injury because they are at high risk, especially ones with high revised cardiac risk indexes and peri-operative erythrocyte transfusion more than 500 ml.